Exploring the Agriculture-Nutrition Linkage in Northern Ghana - Signorelli, Sara; Haile, Beliyou; Kotu, Bekele Hundie (International Food Policy Research Institute, 2017)
Despite progresses over the last few decades, undernutrition is widespread across Africa south of the Sahara. While agricultural interventions have traditionally focused on enhancing yields of few staple crops, there is increased interest on the role of production diversity in enhancing the dietary quality of subsistence farm households. This study examines the effects of on-farm production diversity and productivity on household dietary diversity using primary data from Ghana, where a sustainable intensification program is being implemented. In addition, it assesses possible heterogeneity in the effect of production diversity by market access. Identification is based on instrumental variables ‒ to account for possible simultaneity between production and consumption decisions ‒ and propensity score weighting‒to account for potential self-selection into the program. Both productivity and production diversity positively affect dietary diversity, with the effect of the latter getting stronger the farther away the daily market is, suggesting the importance of production diversity in settings with limited access to markets.